Foreign direct investment in Serbian banking industry: An exploratory study of motives - Marinković Srđan; Ljumović Isidora; Živković Aleksandar (Međunarodni Problemi)
The paper is an attempt to assess relative importance of selected motives for foreign banks entry into Serbian banking market, as well as the changes that followed it, above all in terms of level of competition. We used questionnaires structured according to the main findings that come out of existing theoretical and empirical research on motives for FDI in banking industry. In addition, the goal of this study is to reveal the links between paradigms and theories, which are up to explaining determinants and motives of FDI in banking and the other industries, find common features, peculiarities and use it to refine research methodology.